Anomalously Large Gradients in Version 1 of the "GEODATA 9 SECOND" Digital Elevation Model of Australia, and their Effects on Gravimetric Terrain Corrections - Kirby, Jon; Featherstone, Will (Mapping Sciences Institute Australia, 2001)
Large gradients, when calculated by a first-difference method, have been detected in the 9 arc-second National Digital Elevation Model (DEM) of Australia released by the Australian Surveying and Land Information Group. Gradient values implied by the mean elevations in the DEM between adjacent grid cells of up to 74 have been observed, most notably in Australia?s more mountainous regions in the east. Comparisons with topographic maps indicate that these are anomalous gradients in the DEM that are not present in the actual topography. It is recommended that the first-difference method is used to test DEMs before they are used to compute terrain corrections.